(untitled) (International Journal of Engineering and Computer Science, 2015)
The cloud verifies the authenticity of the series without knowing the user’s identity in the proposed scheme. For the purpose of secured data storage in clouds, we propose a new decentralized access control supporting anonymous authentication. The feature of access control in which only authorized users can decrypt the stored information. In this we prevent replay attacks and also helps in creating, modifying and reading the data stored in clouds. This paper also provides user revocation. The access control scheme and authentication that has been provided is decentralized and robust, whereas the other access control schemes support centralized data in clouds.